Blogging in Beirut : an Ethnography of a Digital Media Practice. - Jurkiewicz, Sarah (Kultur und soziale Praxis., 2018)
Unlike previous media-analytic research, Sarah Jurkiewicz' anthropological study of blogging understands the creation and maintenance of weblogs as a social field and a domain of practice. This approach underlines the significance of blogging in practitioners' daily lives and for their self-understanding. In this context, the notion of publicness enables a consideration of the blogosphere not as a normative, `static' space that actors merely enter, but as produced and constituted by social practices. The vibrant media landscape of Beirut serves as a selection of samples for an ethnographic exploration of blogging.